Developing Dynamic Number Card Game of Number Sense for First Grade Students - Windi Wulandari; Zetra Hainul Putra; Mahmud Alpusari; Dahnilsyah Dahnilsyah; Hartono Tjoe (Universitas Syiah Kuala, 2022)
This study aims to develop a learning media in the form of a dynamic number card game based on number sense as a media for learning mathematics for first graders. This study uses the research and development (RD) with ADDIE model. Data collection techniques were interviews, observation, and questionnaires. The quality of the dynamic number card game was obtained from the validity and practicality test. Expert validation was carried out to evaluate the quality of media and content. The practicality test was conducted one-to-one (3 students) and in small groups (6 students working in small groups). The results showed that the dynamic number card game received a high score of validity from the expert judgment. The students also had positive responses to the practicality of the dynamic number card game in guessing and ordering numbers. The findings indicate that the dynamic number card game has the potential to be used as a medium for learning number sense for first grade students.